2009
DOI: 10.4315/0362-028x-72.7.1419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Radiation on the Quality and Shelf Life of Refrigerated Rainbow Trout (Oncorhynchus mykiss) Fillets

Abstract: The effect of gamma radiation (0, 1, 3, and 5 kGy) on the shelf life of farmed rainbow trout (Oncorhynchus mykiss) fillets that were treated with sodium acetate and vacuum packaged and subsequently stored under refrigeration was studied by measuring microbiological, chemical, and organoleptic changes. Radiation affected populations of bacteria, namely, H2S-producing bacteria and Enterobacteriaceae (P < 0.05). Initial total viable counts of the control samples were ca. 4.41 log CFU/g, whereas the respective cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
10
45
0
Order By: Relevance
“…TVC count at the end of storage for irradiated at 3 kGy, Tio2 nanocomposite+3kGy, at 5 kGy and Tio2 nanocomposite became 4.12, 2.27, 1.91 and 6.41 logs CFU/g respectively. Similar result reported by Oraei, Motalebi, Hoseini and Javan (2010); Mohamed et al (2009) and Moini et al (2009). They concluded that irradiation can reduce survival of TVC in fish fillet.…”
Section: Microbial Assaysupporting
confidence: 84%
See 2 more Smart Citations
“…TVC count at the end of storage for irradiated at 3 kGy, Tio2 nanocomposite+3kGy, at 5 kGy and Tio2 nanocomposite became 4.12, 2.27, 1.91 and 6.41 logs CFU/g respectively. Similar result reported by Oraei, Motalebi, Hoseini and Javan (2010); Mohamed et al (2009) and Moini et al (2009). They concluded that irradiation can reduce survival of TVC in fish fillet.…”
Section: Microbial Assaysupporting
confidence: 84%
“…However, Tio2 nanocomposites caused decrease in pH value during refrigerator storage (P<0.05). A similar trend in irradiation effect on fish, was observed for farmed sea bass, turbot on ice and rainbow trout in refrigerator storage (Papadopoulos, Chouliara, Badeka, Savvaidid & Kontominas, 2004;Moini et al, 2009). …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Other authors have reported similar values in different species (initial and final counts), such as sea bass with counts of 2 and 4.2 log CFU/g (Papadopoulos et al 2003), sea bream with 3.9 and 5.6 log CFU/g (Özden et al 2007) and sardines with 3.5 and 5.08 log CFU/g (Erkan and Özden 2008). The contribution of Enterobacteriaceae to the microflora of fish and its potential spoilage must be taken into consideration especially in the case of polluted water or delay in chilling after catch (Chouliara et al 2004), as well as in the filleting process (Moini et al 2009). Although this group of bacteria can grow at low temperatures, their abundance decreases during ice storage, possibly because their growth rate is lower than in others Gramnegative psychrotrophic spoilers (Bahmani et al 2011).…”
Section: S Putrefaciens Pseudomonas Spmentioning
confidence: 99%
“…The contribution of Enterobacteriaceae to the microflora of fish and its spoilage potential must be taken into consideration especially in the case of polluted water or delay in chilling after catch (Chouliara et al, 2004), as well as in the filleting process (Moini et al, 2009). Although this group can grow at low temperatures, their abundance decreases during iced storage, possibly because their growth rate is lower than that of other Gram-negative psychrotrophic spoilers, making them poor competitors (Bahmani et al, 2011).…”
mentioning
confidence: 99%